Development of a New Method to Predict the Maximum Spread Factor for Shear Thinning Drops - Osorio-Lira, F; Andrade-Pizarro, R (Elsevier Ltd, 2015)
Abstract Drop impact on a solid surface has obtained attention for a variety of industrial processes, such as application of edible coatings by spray application method. In the present work, drop impact behavior of edible coating formulations (ECF) based on gelatin, glycerol and cellulose nanofiber on banana and eggplant epicarps was studied. Drops of ECF were generated from a syringe pump system-controlled, for images a high speed camera was used and the maximum spread diameter was determined with ImageJ program. The models reported in the literature do not predict experimental data of maximum spread factor, because the EFC behave as non-Newtonian fluid, so it was necessary to modify these models by introducing an apparent viscosity at average shear rate (effective viscosity). The inclusion of an effective viscosity significantly improves the prediction of the evaluated models. © 2015 Elsevier Ltd. All rights reserved.